Low doses of ozone alleviate cardiomyocyte ferroptosis induced by hypoxia–reoxygenation injury via the AMPK–mTOR pathway - Yu Ding; Tao Hong (European Journal of Medical Research)
Abstract Background Acute myocardial infarction (AMI), a sudden and dangerous form of cardiovascular diseases (CVDs), induces myocardial hypoxia–reoxygenation (H/R) injury, which exacerbates myocardial damage and potentially results in heart failure. In this study, we explored the effect of low-concentration ozone after hypoxia–reoxygenation injury. Methods CCK-8 assay and flow cytometry wisere performed to assess cell viability. To evaluate ferroptosis, ferroptosis-related protein expression levels, intracellular Fe2+ levels, glutathione (GSH), and reactive oxygen species (ROS) were assessed. We employed Erastin, a known ferroptosis inducer to explore the relationship between ferroptosis and ozone. Meanwhile, we employed the selective AMPK inhibitor dorsomorphin to investigate how the ozone affects AMPK–mTOR pathway. Results The results discovered that an appropriate dose of ozone can effectively mitigate ferroptosis in H9c2 cardiomyocytes induced by hypoxia–reoxygenation. Erastin successfully antagonized the effects of ozone, further confirming ozone’s significant role in regulating ferroptosis. Mechanistically, ozone effectively suppressed intracellular oxidative stress levels, thereby activating the AMPK–mTOR pathway. In addition, dorsomorphin successfully blocked the effects of ozone and exacerbated ferroptosis following hypoxia–reoxygenation, suggesting the regulation of AMPK–mTOR pathway. Conclusions Low-concentration ozone treatment has shown promise in mitigating ferroptosis by regulating the AMPK–mTOR pathway, highlighting its potential as a therapeutic agent for hypoxia–reoxygenation injury.